Container transshipment problems and the solution - László, Vida; Béla, Illés; Bányai, Ágota (Journal of Production Engineering, 2021)
One of the obstacles to the spread of rail-road intermodal freight transport is the lack of efficient container handling equipment on the rail-road hubs. The known and widely used solutions (gantry crane, reach stackers) are apparently not able to increase the volume of intermodal transport. The goal, which is uniformly desired by the professionals, the growth of rail-road intermodal freight transport, can be served by a container transhipment device that allows unit loads to be transferred between road and rail vehicles even under railway contact line. The new container transhipment technology, proposed in the article can be the missing hardware device for physical internet hubs. The highly automated handling robot meets the requirements of Industry 4.0 and Logistics 4.0.